Public Procurement Reforms and Service Delivery in Rubanda District Uganda. - Niwagaba, Ivan (Kabale University, 2024)
The purpose of this study is about Public Procurement Reforms and service delivery in Rubanda District, Uganda. This underlay on the following objectives that is to assess the effect of compliance with procurement rules and procedures on service delivery, evaluate the relationship between procurement forms and service delivery and assess the effect of staffing and functionality of procurement committees on service delivery in Rubanda District. A cross-sectional design was used to undertake the study. The choice of design was in line vith the study objective of obtaining data from a significant portion of the population under study, but also to enabled the researcher get a clear understanding of the effect public procurement reforms have had on service delivery in local government units in general and Rubanda District in particular.Targeting the sample! of 100 respondents, the main data collection instrument of the study used the research questions. The research questionnaire was dusignin likert scale form and it tapped data on the study variables and data analysis involved the use of such tools as frequencies, correlations and regressions to address the research study objectives. Results indicated that there are positive relationships between the Procurement reforms clement and service delivery. The correlations show that the Procurement reforms ispositively related to the service deli very of the institution. This was a clear indication that if the Procurement reforms process is managed efficiently and professionally, thenthis causes an inevitable improvement in the Service Delivery of the institution. Theresearch study thereafter suggests a number of workable recommendations for instance the use or training Programmes to improve the use of the controls in managing theresourcesofthe district and the over all productivity of the employees to cooperation with other key bodies such as other local governments. This shall help the district adopt ideas which haveproved tobe very effective for other local governments that are quite successful in the delivery of service.